A Study of Blood Alcohol Level in Victims of Fatal Road Traffic Accidents in Manipur, India - Tej Bahadur Chhetri; U B Ghaffar; Syed Meraj Ahmed (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Alcohol is well-established risk factors for road traffic deaths around the world. Method:This is a cross-sectional study to assess the prevalence of alcohol consumption among the victims of fatalroad traffic accidents in Imphal, Manipur. A detailed post-mortem examination was carried out among160 victims and blood alcohol concentration was assessed by Cavett test and then quantified by gas liquidchromatography. Result: A total of 40 (25%) cases were found to be positive for alcohol in the blood. Mostof the cases 11(27.5%) occurred in age group of 21-30 years and 41- 50 years, respectively. Maximumnumber of cases 13(32.5%) showed blood alcohol concentration of 90-120 mg% while 7(17.5%) casesshowed readings above 180 mg%. Conclusion: This study found that driving under the influence of alcohol,exponentially increases the risk of having an accident which could be fatal in its outcome.